2014
DOI: 10.1097/wnq.0b013e31828c7410
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Fracture Depression Level and Dural Tear in Patients With Depressed Skull Fracture

Abstract: Introduction: Trauma is the leading cause of morbidity and mortality worldwide, 80% of which is due to head trauma. Simple depressed cranial fractures are being treated conservatively; however, dural tear is an indication of surgical intervention. Computed tomography (CT) scan is the method of choice for initial evaluation of patients with head trauma. This study was designed to evaluate the correlation of dural tear and level of depression in cranial fractures, considering surgical findings as gold standard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The current study reported a significant correlation between high levels of fracture, depression, and dural tear amongTBI patients (12). This evidence demonstrates that dural tear could be a diagnostic factor in patients operated for a depressed skull fracture.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The current study reported a significant correlation between high levels of fracture, depression, and dural tear amongTBI patients (12). This evidence demonstrates that dural tear could be a diagnostic factor in patients operated for a depressed skull fracture.…”
Section: Discussionsupporting
confidence: 68%
“…The mean levels of area, based on CT findings, (12) The numbers show the frequency of patients with these signs. were obtained as 6.92 cm² in patients with intact dura, and 7.2 cm² in patients with dural tear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In closed fractures, surgical management was rarely offered by the majority of respondents. Although there is no available class I evidence for the level of bony depression as an indicator for surgery, evidence suggests that the greater the depression, the higher the likelihood of dural tears, 18 which, in turn, can be indicative of underlying cortical damage. Higher rates of posttraumatic epilepsy have been reported in cases of depressed fractures with dural tears, 19 but this likely reflects cortical damage, and elevation does not appear to negate this risk.…”
Section: Surgical Indicationsmentioning
confidence: 99%